2020
DOI: 10.1007/978-3-030-41568-6_15
|View full text |Cite|
|
Sign up to set email alerts
|

“I do it because they do it”: Social-Neutralisation in Information Security Practices of Saudi Medical Interns

Abstract: Successful implementation of information security policies (ISP) and IT controls play an important role in safeguarding patient privacy in healthcare organizations. Our study investigates the factors that lead to healthcare practitioners' neutralisation of ISPs, leading to noncompliance. The study adopted a qualitative approach and conducted a series of semi-structured interviews with medical interns and hospital IT department managers and staff in an academic hospital in Saudi Arabia. The study's findings rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The greatest security threat is the unauthorized use of the HIS (11 studies). This threat can lead to incident events because of vulnerabilities in the healthcare facilities—for example, lack of security awareness and policy compliance [ 11 , 50 , 58 , 70 , 81 , 82 ], use of multiple entry points to access electronic medical records [ 49 , 65 ] and forgetting to log out after using the HIS at an unattended workstation [ 85 ]. The second-greatest threat is masquerading by insiders, such as staff accessing the HIS without using their own account (seven studies).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The greatest security threat is the unauthorized use of the HIS (11 studies). This threat can lead to incident events because of vulnerabilities in the healthcare facilities—for example, lack of security awareness and policy compliance [ 11 , 50 , 58 , 70 , 81 , 82 ], use of multiple entry points to access electronic medical records [ 49 , 65 ] and forgetting to log out after using the HIS at an unattended workstation [ 85 ]. The second-greatest threat is masquerading by insiders, such as staff accessing the HIS without using their own account (seven studies).…”
Section: Resultsmentioning
confidence: 99%
“…The following factors appeared in two studies: Perceived certainty is derived from GDT, which can examine different acts or processes, such as detection [ 80 ] and punishment [ 73 ]. Two selected studies evaluated the impacts of peer influence and superior influence on different types of security behavior: protection intention [ 70 ] and non-compliance intention [ 82 ]. Both studies revealed that peer and superior influences significantly affect security behavior intentions through individual factors as mediating variables, such as subjective norms [ 70 ] and neutralization techniques [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation